Telepsychotherapy: a leaflet for psychotherapists in the age of COVID-19. A review of the evidence. Issue 3 (2nd October 2021) - Poletti, Barbara; Tagini, Sofia; Brugnera, Agostino; Parolin, Laura; Pievani, Luca; Ferrucci, Roberta; Compare, Angelo; Silani, Vincenzo
ABSTRACT: COVID-19 outbreak imposes the adoption of extraordinary containment measures, including the strict necessity to limit interpersonal contact. Face-to-face psychotherapy collides with this requirement and, above all, it might endanger both therapists and patients' safety. Telepsychotherapy might come to the aid, ensuring therapeutic continuity and the possibility to reach people who might benefit of extra psychological support. Infectious outbreaks have been indeed associated with major psychopathological outcomes. The aim of the present work is to review the most recent experimental evidence about telepsychotherapy, focusing on its effectiveness, possible determinants of efficacy and therapists/patients' attitudes, to rapidly inform psychotherapists. Out of the 857 records found, 18 studies have been included in the review. Our results show that, despite therapists and public's skepticism, telepsychotherapy is a trustworthy alternative to be adopted, which can be used efficaciously to treat common mental-health disorders such as anxiety, depression and post-traumatic distress. As well as in the traditional setting, a higher number of sessions and the proper management of patients' expectations seem to be associated with better outcomes. On the contrary, low familiarity with web-based means of communication and technical issues might reduce specifically the effectiveness of telepsychotherapy.